1992
DOI: 10.1088/0029-5515/32/10/i09
|View full text |Cite
|
Sign up to set email alerts
|

Electron cyclotron current drive experiments on T-10

Abstract: The results of electron cyclotron current drive experiments on the T-10 tokamak are presented.The total RF power was up to 2.5 MW, the electron temperature was up to 7 keV and the maximum driven current was 110 kA. The current drive efficiency qcD was approximately 0.1 A/W. The value of qcD and its dependence on the plasma parameters agree satisfactorily with the linear theory, corrected for the finite confinement time of resonant electrons. In discharges with large beta poloidal, ,9, = 3, complete replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 13 publications
2
27
0
3
Order By: Relevance
“…Because of the different regions of phase space with which ECH interacts, simulations show that the accelerated electrons remain generally more collisional than in the case of LHCD, resulting in weaker HXR emission. This was confirmed in early measurements, which also showed that more suprathermal emission is observed in the case of ECCD, 43,44 which targets electrons with high parallel velocity, than with pure ECH. These measurements, particularly on the T −10 tokamak, were used to study the decay time upon power switch-off, 43 again concluding that cross-field transport was negligible.…”
Section: Hard-x-ray Bremsstrahlungsupporting
confidence: 55%
See 2 more Smart Citations
“…Because of the different regions of phase space with which ECH interacts, simulations show that the accelerated electrons remain generally more collisional than in the case of LHCD, resulting in weaker HXR emission. This was confirmed in early measurements, which also showed that more suprathermal emission is observed in the case of ECCD, 43,44 which targets electrons with high parallel velocity, than with pure ECH. These measurements, particularly on the T −10 tokamak, were used to study the decay time upon power switch-off, 43 again concluding that cross-field transport was negligible.…”
Section: Hard-x-ray Bremsstrahlungsupporting
confidence: 55%
“…This was confirmed in early measurements, which also showed that more suprathermal emission is observed in the case of ECCD, 43,44 which targets electrons with high parallel velocity, than with pure ECH. These measurements, particularly on the T −10 tokamak, were used to study the decay time upon power switch-off, 43 again concluding that cross-field transport was negligible. 59 This conclusion was challenged when measurements were performed with ECCD on TCV, which features extremely high ͑up to 40 MW/ m 3 ͒ ECH power densities.…”
Section: Hard-x-ray Bremsstrahlungsupporting
confidence: 55%
See 1 more Smart Citation
“…However, as a result of studying the energy keeping during variation in the plasma parameters in a wide range of their values when introducing an additional microwave radiation, it was shown that the energy lifetime τ E significantly decreases with increasing introduced radiation power P : τ E ∝ P −0. 6 . The results of the study of the transport coefficients during the ECR plasma heating are reviewed in [4].…”
Section: Plasma Heating Under the Electron-cyclotron Resonancementioning
confidence: 99%
“…For this purpose, the further plasma-heating experiments in the T-10 tokamak were conducted using the second ECR harmonic. In this case, the waves had extraordinary polarization, i.e., the X mode was used [5]. In the above-mentioned experiments, the gyrotrons with the frequency f = 140 GHz, power P HF ≈ 0.5 MW, and a microwave-pulse duration of up to 400 ms were used.…”
Section: Plasma Heating Under the Electron-cyclotron Resonancementioning
confidence: 99%